Additive manufacturing of dental material parts via laser melting deposition: A review, technical issues, and future research directions. (April 2022) - Selvaraj, Senthil Kumaran; Prasad, Shubham Kumar; Yasin, Sayyed Yassir; Subhash, Ulavala Sowri; Verma, Pakalapati Saketh; Manikandan, M.; Dev, S. Jithin
Abstract: Dental decays are quite a recurring issue in today's busy life of people around the world; hence, its use is very standard practice. While dental implant development, materials, and procedures have significantly expanded and are predicted, it would further broaden throughout the coming decades. Much work is associated with the research to use new biomaterials, implant design, surface alteration, and functionalisation to make long-term care affordable and with better results. This article offers a short historical development of dental implants. It also gives information about the types of implants produced and the commonly used criteria throughout the implant design. Finally, this paper also discusses the various materials used in the coming future with some reasonably new additive manufacturing processes that have never been used before.